2020
DOI: 10.24018/ejfood.2020.2.4.80
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake and Prevalence of Dental Caries among Five-Year-Old Children in Urban and Rural Areas of Uasin-Gishu County, Kenya

Abstract: Dental caries is a major public health problem associated with diet and nutrition affecting 60-90% of children globally with the burden in both industrialized and less industrialized countries undergoing nutrition transition. The aim of this study was to assess the relation between the dietary intake and nutritional status on dental caries prevalence of 5-year-old school children in urban and rural areas of Uasin-Gishu County.  In this study, 382 five year old children and their parents/caregivers were sampled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…2,42 This finding was contrary to the high prevalence of stunting, which can also be found in this review. [21][22][23][24][25][26]30,31,35,40,43 Another optimal breastfeeding in-dicator has its role in linking this phenomenon. Prolonged breastfeeding is a complex behavior that cannot be separated from other aspects such as good frequency, method, and time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,42 This finding was contrary to the high prevalence of stunting, which can also be found in this review. [21][22][23][24][25][26]30,31,35,40,43 Another optimal breastfeeding in-dicator has its role in linking this phenomenon. Prolonged breastfeeding is a complex behavior that cannot be separated from other aspects such as good frequency, method, and time.…”
Section: Discussionmentioning
confidence: 99%
“…Six studies (n ¼ 6) found poor initiation and diversity of complementary foods. 18,27,30,32,35,37 Five studies (n ¼ 5) found high sugar consumption, with the highest prevalence rates from Athavale et al (52.4%). 7,20,21,24,34 ►Table 4 shows that mothers had shown poor complementary feeding practices and high intake of sugary foods for their children.…”
Section: Maternal Feeding Practicesmentioning
confidence: 95%
See 1 more Smart Citation